Analysis of the Application of Value Added Tax Calculation and Reporting at PT. Darpadina Sumber Abadi (DSA) in 2022 - Meiriska, Meiriska; Nasrulla, Nasrulla; Rosida, Siti Ayu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to analyze the implementation of VAT calculations, deposits, reporting and recording at PT. Darpadina Sumber Abadi 2022 and its conformity with the Law on Harmonization of Tax Regulations (UU No.7 of 2021), Minister of Finance Regulation number 63/PMK.03/2021, and Minister of Finance Regulation number 63/PMK.03/2021 and also the principles applicable accounting. The analysis in this research uses qualitative methods with descriptive observations that collect and analyze the condition of subjects or objects in the form of institutions based on evidence and facts from research subjects. The data used consists of the 2022 Period VAT SPT, 2022 Input and Output Tax Invoices, and the 2022 Recording Journal. Calculation and reporting of PT Value Added Tax. Darpadina Sumber Abadi is in accordance with applicable laws. From the calculation results, PT Darpadina Sumber Abadi experienced an underpayment because the Output Tax was greater than the Input Tax. If there is an underpayment, PT Darpadina Sumber Abadi will make a deposit at the end of the following month